Crazy busy : a (mercifully) short book about a (really) big problem - DeYoung, Kevin (Wheaton, Illinois : Crossway, 2013)
Kevin DeYoung addresses the busyness problem head on in his newest book, Crazy Busy--and not with the typical arsenal of time management tips, but rather with the biblical tools we need to get to the source of the issue and pull the problem out by the roots. --from publisher description
Hello, my name is busy -- Here, there, and gone: three dangers to avoid -- The killer p's--diagnosis #1: you are beset with many manifestations of pride -- The terror of total obligation--diagnosis #2: you are trying to do what God does not expect you to do -- Mission creep--diagnosis #3: you can't serve others without setting priorities -- A cruel kindergarchy--diagnosis #4: you need to stop freaking out about your kids -- Deep calls to deep--diagnosis #5: you are letting the screen strangle your soul -- Rhythm and blues--diagnosis #6: you'd better rest yourself before your wreck yourself -- Embracing the burdens of busyness--diagnosis #7: you suffer more because you don't expect to suffer at all -- The one thing you must do.
Includes bibliographical references and indexes
Keywords: Time management -- Religious aspects -- Christianity; Time management -- Religious aspects -- Christianity